19.7k views
4 votes
Use integration by parts to find the integrals in Exercise.
∫(x+6)ex dx.

User Nvoigt
by
4.4k points

1 Answer

3 votes

Answer:


\displaystyle \int {(x + 6)e^x} \, dx = (x + 5)e^x + C

General Formulas and Concepts:

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Integration

  • Integrals
  • [Indefinite Integrals] Integration Constant C

Integration Property [Multiplied Constant]:
\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx

Integration by Parts:
\displaystyle \int {u} \, dv = uv - \int {v} \, du

  • [IBP] LIPET: Logs, inverses, Polynomials, Exponentials, Trig

Explanation:

Step 1: Define

Identify


\displaystyle \int {(x + 6)e^x} \, dx

Step 2: Integrate Pt. 1

Identify variables for integration by parts using LIPET.

  1. Set u:
    \displaystyle u = x + 6
  2. [u] Basic Power Rule [Derivative Property - Addition/Subtraction]:
    \displaystyle du = dx
  3. Set dv:
    \displaystyle dv = e^x \ dx
  4. [dv] Exponential Integration:
    \displaystyle v = e^x

Step 3: Integrate Pt. 2

  1. [Integral] Integration by Parts:
    \displaystyle \int {(x + 6)e^x} \, dx = (x + 6)e^x - \int {e^x} \, dx
  2. [Integral] Exponential Integration:
    \displaystyle \int {(x + 6)e^x} \, dx = (x + 6)e^x - e^x + C
  3. Factor:
    \displaystyle \int {(x + 6)e^x} \, dx = e^x(x + 6 - 1) + C
  4. Simplify:
    \displaystyle \int {(x + 6)e^x} \, dx = (x + 5)e^x + C

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Integration

User Tarkh
by
4.7k points